2022
DOI: 10.1097/icl.0000000000000888
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Lens Thickness and Corneal Edema Under Open Eye Conditions

Abstract: Purpose:To examine the relationship between lens thickness and central corneal edema during short-term open-eye scleral lens wear, and to compare these empirical edema measurements with theoretical modelling.Methods:Nine participants (mean age 30 years) with normal corneas wore scleral lenses {Dk 141×10−11 cm3 O2 [cm]/([sec] [cm2] [mm Hg])} under open-eye conditions on separate days with nominal center thicknesses of 150, 300, 600, and 1,200 μm. Epithelial, stromal, and total corneal edema were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This finding is consistent with previous experiments, which revealed that substantial thickness increases for high Dk scleral lenses did not result in significant changes in central corneal oedema in the short term. For example, Fisher et al 12 reported a 1% increase in central corneal oedema under open eye conditions when increasing the centre thickness of a scleral lens (Dk 141) from 150 to 1200 μm. Together, these findings indicate that during scleral lens wear (with or without an additional reverse piggyback soft lens), the major barrier to atmospheric oxygen reaching the cornea is the thickness and oxygen permeability of the fluid reservoir beneath the scleral lens (Dk of tears or saline ~80), and the lack of tear exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous experiments, which revealed that substantial thickness increases for high Dk scleral lenses did not result in significant changes in central corneal oedema in the short term. For example, Fisher et al 12 reported a 1% increase in central corneal oedema under open eye conditions when increasing the centre thickness of a scleral lens (Dk 141) from 150 to 1200 μm. Together, these findings indicate that during scleral lens wear (with or without an additional reverse piggyback soft lens), the major barrier to atmospheric oxygen reaching the cornea is the thickness and oxygen permeability of the fluid reservoir beneath the scleral lens (Dk of tears or saline ~80), and the lack of tear exchange.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a reverse piggyback lens system for a scleral lens, the addition of a soft lens acts as an additional barrier to oxygen, with no impact on tear exchange since the soft lens does not alter the interaction between the scleral landing zone and conjunctiva. Since corneal oxygen delivery is compromised during scleral lens wear due to the increased fluid reservoir thickness, 11 increased lens thickness 12 and reduced tear exchange 13 compared with other contact lens designs, piggybacking a scleral lens should be used with caution in clinical practice, typically as a last resort after exhausting other possible solutions to address poor front surface wettability.…”
Section: Introductionmentioning
confidence: 99%
“…On average, a single 0.3‐mm‐diameter peripheral lens fenestration did not alter central corneal oedema compared to a non‐fenestrated highly oxygen‐permeable lens after correcting for variations in the initial central fluid reservoir thickness and lens thickness between the two conditions. This could potentially be attributed to the significantly lower oxygen permeability of the fluid reservoir (Dk 80) compared to that of the lens material (Dk 141), since previous work 13 has demonstrated that large variations in scleral lens thickness have substantially less impact upon corneal oedema than variations in central fluid reservoir thickness. No significant difference was observed between the fenestrated and non‐fenestrated lens for total (both raw (t 8 = 2.31, p = 0.86) and corrected (t 8 = 2.31, p = 0.81)), epithelial (t 8 = 2.31, p = 0.82) or stromal (t 8 = 2.31, p = 0.92) corneal oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Due to small differences in the initial fluid reservoir thickness and the lens thickness between the fenestrated and non‐fenestrated lens conditions, a series of corrections were applied to each participant's total corneal oedema data, based on measurements obtained in previous experiments, which examined the magnitude of central corneal oedema during open‐eye non‐fenestrated scleral lens wear as a function of initial fluid reservoir thickness 16 and lens thickness 13 . Table 1 outlines this correction process for one participant as an example.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation